Literacy and Prosody: The Case of Low‐literate Senegalese Learners of L2 Italian - Maffia, Marta; De Meo, Anne (LESLLA Symposium Proceedings, 2015)
The influence of L1 literacy on the acquisition of L2 oracy has recently become one of the interests of SLA research. However, what is still missing is an exploration of the development of L2 prosodic competence by low-literate adults learners. To fill this gap, in the present study Senegalese learners of L2 Italian were involved. In Senegal, where literacy acquisition is usually absent in the L1 (mostly Wolof), it is possible to acquire it in French or Arabic, albeit the educational models of the French and Koranic schools are quite different. In French schools writing and reading practices are favored, whereas in Koranic schools speaking and listening abilities are mostly practiced by reciting the Koran. In order to understand the relationship between L1 literacy and L2 oracy in the case of low-literate Senegalese learners of L2 Italian and to verify if the different educational models proposed in Senegal influence L2 prosodic competence even of low-educated learners, perceptual and spectroacoustic analyses were conducted on a corpus of utterances produced by 20 Senegalese and collected through an Elicited Imitation task. Results show a higher level of textual accuracy in French school learners’ productions while Koranic school learners show a more skillful reproduction of intonation and rhythm of different Italian speech acts.